Determination of ten arsenic compounds in poultry food by high performance liquid chromatography-inductively coupled plasma mass spectrometry - ZHENG Chenyang; TANG Yun; HAN Jianlong; TAN Ying; MA Bingjie; WU Pinggu (Zhongguo shipin weisheng zazhi, 2022)
ObjectiveTo establish a method for the determination of arsenic compounds in poultry food by high performance liquid chromatography-inductively coupled plasma mass spectrometry（HPLC-ICP-MS）.MethodsThe sample was microwave assisted extracted by 10% methanol and 1% nitric acid．Ten arsenic compounds were separated by DIonexIonPac As7（4 mm×250 mm） anion exchange column with 0.5-200 mmol/L ammonium carbonate for gradient elution.ResultsThe linear ranges for 10 arsenic compounds were between 1-20 μg/L with the linear coefficients（r） more than 0.999 0，and the detection limits of the method were between 0.24-0.80 μg/kg. The relative standard deviations （RSDs） of precision ranged from 1.0% to 5.7%. The recoveries were 83.77%-114.21% in chicken and beef substrate， spiked with the three levels.ConclusionWith high sensitivity， simplicity for pretreatment， good reproducibility and accuracy， the method was suitable for the determination of ten arsenic compounds in poultry food.